Korelasi Point Load Index dan Uniaxial Compressive Strength pada Satuan Batupasir dan Batulempung Formasi Latih untuk Penentuan Koefisien Kekuatan Batuan di Pit X Tambang Batubara PT Berau Coal, Kalimantan Timur - Yan Adriansyah; Guruh Krisnantara; Kurniawan Setiadi (Jurnal Geomine, 2021)
Physical and mechanical properties of rock for engineering purposes are indispensable for any civil/construction, mining and other engineering requirment. The results of the uniaxial compressive strength (UCS) test are very much needed in various geotechnical analyzes or engineering, in particular in the mining industry in relation to the calculation of the pit slope design and other mining infrastructure. Rock samples used in this study were obtained from the results of geotechnical drilling (full core drilling). The rock engineering properties test to obtain UCS and PLI values was carried out in the laboratory. Testing the rock hardness index using the point load index (PLI) can be done more quickly, cheaply, practically and can use rock samples with a variety of sample shapes.         The focus and object of the research are mudstone and sandstone units as part of the Lati Formation. These two types of layers are the most dominant rock types as a constituent of the pit slopes in the research area. To ensure that the correlation results are in accordance with the rules of scientific research, the distribution of UCS and PLI data from laboratory test results is verified using a statistical approach / testing. Correlation and analysis between the two rock engineering properties test results are very useful for geotechnical analysis data input. The coefficient or constant values obtained can be used to determine the rock strength values used in various geotechnical analyzes so that the analysis can be carried out more efficiently, effectively and quickly and can support geotechnical engineering work.